Upper Oligocene-Miocene clinoforms of the foreland Austral Basin of Tierra del Fuego, Argentina: Stratigraphy, depositional sequences and architecture of the foredeep deposits - Ponce, Juan Jose (2008)
The Upper Oligocene-Miocene deposits of the foreland Austral Basin of Tierra del Fuego represent the youngest foredeep fill, developed in front of the adjacent fold and thrust belt. They consist of superbly exposed, sub-horizontal clastic successions of more than 600 m of sedimentary thickness. The study of 11 sections by means of facies analysis and sequence stratigraphic criteria enabled the identification of five depositional sequences (SI-SV), bounded by unconformities (dI-dV) involving hiatuses of different magnitudes. The basal sequence (SI) includes two members: A, mudstone dominated, deposited by cohesive flows; and B, glauconite-rich, sandstone dominated, deposited by episodic turbidity currents. The remaining sequences (SII-SV) are composed of complex arrangements of fine conglomerates, coarse- to fine-grained sandstones, and mudstones that were deposited mainly by hyperpycnal flows. The basal unconformities of the SI to SIV involve minor hiatuses, while that of the SV is a major order unconformity. Two types of clinofom geometries are recognized in the foredeep sequences. Type a clinoforms present a wedge shaped geometry and characterize the foredeep infill during the compressional tectonic regime. Regarding this clinoform type, SI is situated closer to the orogen and shows variations in the bedding dip with development of internal unconformities. SII to SIV are situated towards the foreland and are characterized by subhorizontal conformable beds of large lateral extension. Type b clinoforms, with sigmoidal geometry, show a clear northeast progradation related to a progressive foredeep fill under tectonic quiescence. This clinoform type characterizes the deposits in SV. The recognition of hyperpycnites and different types of clinoform geometries in these sequences incorporates new concepts in reservoir prospects, which are critical for the evaluation of the petroleum system in the Austral Basin.